Impact of NOTCH1 polymorphisms on liver cancer in a Chinese Han population. Issue 9 (3rd May 2023) - Wang, Baofeng; Ma, Xiaobin; Zhang, Wenjie; Li, Liang; Zan, Ying; Zhan, Jianshui; Guo, Xufeng; Lei, Ming; Ma, Hongbing
ABSTRACT: NOTCH1, a member of the Notch family, is up-expression in advanced liver cancer (LC) patients and is associated with tumor sizes, tumor stage, metastasis, and invasion. A few studies have discovered the contribution of NOTCH1 variants to LC risk. Our purpose was to assess the relationship of NOTCH1 rs10521, rs2229971, and rs4489420 to LC risk. We enrolled 709 LC patients and 708 healthy controls. Genotyping was determined through the Agena MassARRAY system. Multiple genetic models by logistic regression were useful for odds ratios (ORs) with 95% confidence intervals (CIs). Rs10521-G (p = 0.009, OR = 0.75, 95% CI: 0.61–0.93), rs2229971-A (p = 0.023, OR = 0.81, 95% CI: 0.67–0.97), and rs4489420-A (p = 0.014, OR = 0.38, 95% CI: 0.16–0.85) might be protective factors for LC occurrence in the Chinese Han population, especially rs10521 and rs2229971 (false-positive report probability (FPRP) <0.2 and statistical power >90%). Interestingly, stratified analysis displayed that the contribution of NOTCH1 polymorphisms to LC risk might be associated with gender, age, smoking, and drinking. Our data first determined that NOTCH1 rs10521-G, rs2229971-A, and rs4489420-A might be protective factors for LC susceptibility.